An Analysis of Grammatical Errors on Students' Writing - Banjar Putri Kumala; Siti Aimah; Muhimatul Ifadah (Universitas Muhammadiyah Semarang, 2018)
This study was conducted to find out the grammatical errors on students’ writing. Grammatical errors were analyzed based on surface strategy taxonomy by Dulay, Burt, and Krashen. It consisted of four types, they were omission, addition, misformation, and misordering. There were 27 students that became the subject of this research. The purpose of this research was to identify and describe the dominant types of grammatical errors on students’ writing and to know to what extent the factors cause grammatical errors on students’ writing. Qualitative and quantitative were chosen as the research design. Library research, analysis, documentation, writing test result, questionnaire, and interview were used as the instruments of the data collection. The result of this research showed that the number of errors occurred was 810 errors. Omission errors had the biggest percentage with the percentage of 37%, followed by addition errors with the percentage of 32%. Misformation errors was in the third position with the percentage of 30% while misordering errors became the lowest errors with the percentage of 1%. The factors causing errors were carelessness (73%), first language interference (61%), translation (67%), teacher’s explanation and students’ incomprehension about grammar. Based on the result of the data, the more factors faced by the students, the more frequency of errors on writing occurred. Therefore, the teacher should recognize the students’ errors and encourage the students to learn grammar.